Pengaruh Self-Efficacy terhadap Pemahaman Konsep Matematika Siswa Pada Pembelajaran Model Discovery Learning - Rahmi, Rahmi; Febriana, Rina; Putri, Gianti Elsa (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
Understanding the concept of students is still low and student self-efficacy is still not the background of this study. The research objective was to determine the understanding of students 'mathematical concepts and determine the effect of self-efficacy on students' conceptual understanding after applying the Discovery Learning model. This type of research is a pre-experiment with a pre-test and post-test group design test. Data analysis using simple linear regression analysis, correlation analysis and t test. Based on the results of data analysis, understanding the mathematical concepts of students has increased with the criteria of being. Questionnaire analysis using the N-Gain formula and obtained student self-efficacy also experienced an increase in the criteria of being. Furthermore, the significance test of the correlation coefficient is obtained tcount < ttable, it can be concluded that self-efficacy by applying the Discovery Learning model influences the understanding of mathematical concepts in students of class XI MIA 1 Solok Selatan N 5 but not significant.